Serpentine [compact disc, unabridged] : an Alex Delaware novel - Kellerman, Jonathan (Alex Delaware novels, 2021)
LAPD homicide lieutenant Milo Sturgis is a master detective. He has a near perfect solve rate and he's written his own rulebook. Some of those successes have involved his best friend, the brilliant psychologist Alex Delaware. But Milo doesn't call Alex in unless cases are 'different.' This murder warrants an immediate call: Milo's independence has been compromised as never before, as the department pressures him to cater to the demands of a mogul. A mega-rich young woman obsessed with reopening the coldest of cases: the decades-old death of her mother. The facts describe a likely loser case: a mysterious woman found with a bullet in her head in a torched Cadillac that has overturned on treacherous Mulholland Drive. No physical evidence, no witnesses, no apparent motive. A slew of detectives have already worked the job and failed. But as Delaware and Sturgis begin digging, the mist begins to lift. Too many coincidences. They soon discover, very real threats are lurking in the present.